GAMA (La’bul Istimā’ Al-‘Araby) ‘Alā Asasi Ta’allumi Aṡ- Ṡaqāfah Al-Waṭaniyyah Li Mahārati Al-Istimā’ Al-‘Araby - Novita Kusumadewi; Aziz Fajar Nurizki; Khaulah Nabila Amjad; Zukhaira Zukhaira (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2018)
AbstractArabic in Indonesia is one of the foreign languages taught by students in educational institutions, whether formal or informal, from primary school, middle school, high school even in university. If we learn the language of the country, then we have to learn its culture for sure. Education on the basis of culture is a process where the culture information of the students was more extensive by means of new information about culture and other language or foreign. At the same time, children are aware of the specific signs of their culture and language. Language education is a success if students have mastered the four language skills. The four language skills include listening skills, speech skills, reading skills and writing skills. Learning Arabic is arranged in order from listening skill to writing skill. Although learning Arabic in Indonesia has been practiced for centuries, learning the skill of listening and the skill of Arabic speech is still less effective and incurious among the learners. Based on the previous problem, it needs to be treated. It is the various educational means used by teachers and students to learn the listening skills. It is GAMA (Arabic listening game) which is not only about learning and training in the skill of listening, but the material that is based on culture because learning the language does not deny the learner to learn the language culture mentioned.Keywords: GAMA, Listening Skill, Teaching Aids, Education on the Basis of National Cultures.  GAMA )لعب الاستماع العربي( على أسس تعلم الثقافة الوطنية لمهارة الاستماع العربينوفيتا كوسوما داوي، عزيز فجار نور الرزق، خولة نبيلا أمجاد، وزهيرجامعة حكومية سيمارانجnvtkusumadewi@gmail.com, azizfajar@gmail.com, khaulahnabila@gmail.com, zukhaira_unnes@yahoo.com الملخصاللغة العربية في إندونيسيا هي إحدى اللغات الأجنبية التي يتعلمها التلاميذ في المؤسسات التعليمية سواء كانت رسميا أو غير رسمي من مستوى المدرسة الإبتدائية، والمدرسة المتوسطة، والمدرسة الثانوية حتى في الجامعة. إذا نتعلم لغة البلد، فطبعا لا بد علينا أن نتعلم الثقافة. التعليم على أسس الثقافة هو عملية حيث كانت معلومات الثقافة من الطلاب أشد واسعة بوسيلة المعلومات الجديدة عن الثقافة واللغة الأخرى أو الأجنبية. وهذا الحال في نفس الوقت يذكر إدراك الأولاد عن الدلائل الخاصة من ثقافتهم ولغتهم. يعد تعليم اللغة نجاحا إذا كان الطلاب استوعبوا المهارات اللغوية الأربعة. وتحتوي  المهارات اللغوية الأربعة على مهارة الاستماع، ومهارة الكلام، ومهارة القراءة، ومهارة الكتابة. تعلم اللغة العربية يقام بالترتيب من مهارة الاستماع حتى مهارة الكتابة. رغم أن تعلم اللغة العربية في إندونيسيا جرى على القرون، تعلم مهارة الاستماع ومهارة الكلام العربي مازال قليل الاهتمام وقليل المركز. بناء على المشكلة السابقة، يحتاج إلى العلاج وهي الوسائل التعليمية المتنوعة التي يستفيدها المعلمون والطلاب في تعلم مهارة الاستماع. وهي GAMA  (لعب الاستماع العربي) حيث فيه ليس فقط عن التعلم و التدريب على مهارة الاستماع، ولكن فيه المادة مؤسسة على الثقافة لأن تعلم اللغة لا ينكر المتعلم على تعلم ثقافة اللغة المذكورة.المفتاح الرئيسي: GAMA  (لعب الاستماع العربي)، مهارة الاستماع، الوسائل التعليمية، التعليم على أسس الثقافة الوطنية